2008
DOI: 10.1111/j.1095-8649.2008.02020.x
|View full text |Cite
|
Sign up to set email alerts
|

Autumnal shift from diurnal to nocturnal peaking feeding activity of Rutilus rutilus in boreal lake littoral zones

Abstract: The possibility that the feeding activity of roach Rutilus rutilus shows an autumnal shift towards hours of lower light intensity in shallow and illuminated habitats in temperate watercourses as a consequence of relatively increasing daytime predation risk was tested in a littoral zone of a large boreal lake using trapping experiments. Autumnal feeding activity of R. rutilus first showed a striking shift from day to twilight when water temperature fell from 20 to 10°C, and a low but steady night activity preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…High fish activity at dusk and dawn and low activity at night corresponded well to active telemetric (Jacobsen et al, 2002(Jacobsen et al, , 2004Zamora and Moreno-Amich, 2002;Hautala, 2008) and hydroacoustic (Lilja et al, 2003) studies, as well as to passive trapping (Baade and Fredrich, 1998) and gillnetting (Olin and Malinen, 2003;Olin et al, 2004;Vašek et al, 2009) studies on common European fish.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…High fish activity at dusk and dawn and low activity at night corresponded well to active telemetric (Jacobsen et al, 2002(Jacobsen et al, , 2004Zamora and Moreno-Amich, 2002;Hautala, 2008) and hydroacoustic (Lilja et al, 2003) studies, as well as to passive trapping (Baade and Fredrich, 1998) and gillnetting (Olin and Malinen, 2003;Olin et al, 2004;Vašek et al, 2009) studies on common European fish.…”
Section: Discussionmentioning
confidence: 52%
“…Activity peaks lasted longer in the turbid reservoir, which could be explained by the higher general activity of fish in a turbid environment (Andersen et al, 2008;Hazelton and Grossman, 2009). Also, it could be connected to a shift in diel activity pattern in varying water temperatures, as observed by Hautala (2008). During the experiments, the water temperature at the turbid reservoir was about 10 • C lower than that in the clear reservoir.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…It contradicts the results of Persson (1986), who found that P. fluviatilis had a higher capture rate than R. rutilus at 12 and 16° C, but this difference may be due to the fact that larger fish were used in Persson's (1986) experiments and may not be quite comparable. Hautala (2008) has shown by means of field experiments with baited traps that R. rutilus feeding activity is less affected by temperature than by light regime in autumn, and Linløkken & Haugen (2006) found that gillnet catches of P. fluviatilis were low, suggesting low swimming activity at temperature <10° C in boreal lakes in south‐eastern Norway. Rutilus rutilus catches were less affected by temperature, indicating relatively higher activity of R. rutilus compared with P. fluviatilis at low temperatures, which corresponds to Neuman's (1979) results along the Swedish coast of the central Baltic Sea.…”
Section: Discussionmentioning
confidence: 99%